Gender and wavefront higher order aberrations: Do the genders see the world differently? - Reilly, CD; Blair, MA (Nepalese Journal of Ophthalmology, 2010)
Introduction: Wavefront sensing technology has emerged as a means to advance our understanding of high-order aberrations of the human eye. Purpose: To evaluate the differences in ocular high-order aberrations between males and females and the distribution of high-order aberrations in males and females. Subjects and methods: 3,597 eyes (1,029 female and 2,568 male) of 1,874 patients who obtained wavefront measurements performed using the VISX Wavescan device were included in this study. Mean RMS (root mean square) values of high-order aberrations (HOAs) and the mean of each Zernike polynomial from the second to the sixth order were calculated from multiple scans of each eye. Analysis was performed to assess the association between HOAs and gender, and symmetry of HOAs between eyes in both males and females. Results: Overall HOA did not differ significantly between males and females (p= 0.93). Overall HOA did not differ between left eyes (p=0.852) or right eyes (p=0.76). Individual Zernike polynomials did reveal a significant difference between male and female eyes: Z14 (Tetrafoil x, p=.036); Z16 (Secondary Trefoil y, p=0.015); Z24 (Secondary Spherical, p=0.003); Z25 (Tertiary Astigmatism x, p=0.010); and Z26 (Secondary Tetrafoil x, p=0.004). Conclusion: Overall HOA does not differ between the genders; however, individual HOA Zernike terms do demonstrate statistically significant differences between males and females. This is the first such study to describe these differences. The clinical significance of these differences has yet to be determined. Keywords: refractive surgery; high-order aberrations; cornea; gender DOI: 10.3126/nepjoph.v1i2.3680 Nep J Oph 2009;1(2):85-89